Aplikasi Geotube sebagai Konstruksi Alternatif Penanggulangan Erosi Akibat Gelombang Pasang Bono - Andryan Suhendra; Ganny Saputra; Eric Rinaldo Kodrat (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Bono tidal current leads to silting of the river estuary. The impact is a change in river line of Muda Island due to erosion and deposition. One alternative construction to overcome such this erosion problem of isGeotube, a construction system that combines geosynthetic material for blanket and sand slurry material for filler. Analysis is performed to ensure the system is feasible through the use of Geocops software to determine the type of suitable geosynthetic material and other parameters such as pump pressure. Another analytical calculation performed is the calculation of the stability of global construction through the use of Slope/W software and the approximate amount of consolidation decrease occurred using one-dimensional consolidation theory, published by Terzaghi. This article also presents the process of field implementation including various obstacles encountered and the solutions. From the results of the analysis and the field implementation, it can be concluded that the use of Geotube system on this project provides satisfactory results and can be relied upon as an alternative construction of erosion problems.